Pengaruh Beauveria bassiana terhadap Mortalitas Semut Rangrang Oecophylla smaragdina (F.) (Hymenoptera: Formicidae) - Mochammad Sodiq; Dwi Martiningsia (Perhimpunan Entomologi Indonesia, 2009)
The study was conducted at the laboratory and cacao plantation in Kaliwining Jember, during August to November 2008. The objective of this research was to study the effect of B. bassiana on the mortality of larvae, pupae and adults of O. smaragdina. A factorial completly randomized design was used in the laboratory experiment. Two factors were tested in the experiment, the first factor was spore concentration; the second factor was the stadia of the ants (larva, pupa and adult). The experiment was replicated, 4 (four) times. The field research used a randomized block complete design with four treatments and four replications. Results of this study showed that B. bassiana was the mortality source of larva, pupa and adult stages of O. smaragdina. A concentration of 108 spores/ml B. bassiana was effective to control larvae and pupae of O. smaragdina.